2013
DOI: 10.3926/ic.377
|View full text |Cite
|
Sign up to set email alerts
|

The gamification and the enrichment of innovation practices in the firm: an analysis of experiences

Abstract: ResumenObjeto: Descripción de las prácticas de gamificación en la empresa y análisis de su influencia en los resultados a través del estudio y comparación de experiencias.Diseño/metodología/enfoque: Análisis de experiencias desde diferentes teorías de empresa. Aportaciones y resultados:Mostrar a través de ejemplos reales que la utilización de la gamificación lleva a mejores resultados en las organizaciones.Limitaciones/implicaciones: Acceso a la información de los pocos casos aún existentes en nuestro entorno … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
2
0
11
Order By: Relevance
“…The data on the frequency with which each topic has been addressed are contained in the following table (Table 5). The research topic that most frequently appears in the papers analysed involves performance (21.51%), which is studied from the perspective of different theories, such as Contingency theory (Ceci & Masini, 2011), Linear programming (Geng, Chu, Xue & Zhang, 2011), Resource dependence theory (Shah, Jajja, Chatha & Farooq, 2020;Chang et al, 2019), Agency theory (Datta, 2020), Game theory (Arabi, Mansour & Shokouhyar, 2018;Gómez & Heredero, 2013;Hezarkhani, 2017;Lee et al, 2016) and Resource-based theory (Fang, Palmatier & Steenkamp, 2008;Yan et al, 2020;Zhang et al, 2019), These results are consistent with those reported by Wang, Lai, and Shou (2018), identifying numerous studies that analyse the impact that servitization has on performance.…”
Section: Discussion Of Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The data on the frequency with which each topic has been addressed are contained in the following table (Table 5). The research topic that most frequently appears in the papers analysed involves performance (21.51%), which is studied from the perspective of different theories, such as Contingency theory (Ceci & Masini, 2011), Linear programming (Geng, Chu, Xue & Zhang, 2011), Resource dependence theory (Shah, Jajja, Chatha & Farooq, 2020;Chang et al, 2019), Agency theory (Datta, 2020), Game theory (Arabi, Mansour & Shokouhyar, 2018;Gómez & Heredero, 2013;Hezarkhani, 2017;Lee et al, 2016) and Resource-based theory (Fang, Palmatier & Steenkamp, 2008;Yan et al, 2020;Zhang et al, 2019), These results are consistent with those reported by Wang, Lai, and Shou (2018), identifying numerous studies that analyse the impact that servitization has on performance.…”
Section: Discussion Of Resultssupporting
confidence: 75%
“…Hezarkhani (2017) uses Game theory to manage these relationships, seeking to coordinate the parties' efforts to optimise the gains made by the entire system, instead of focusing on the decision-making problems they face. Gómez & Heredero (2013) consider that gamification leads to an improvement in users' experience, pursuing the aim of motivating, achieving, promoting and upholding greater engagement with the features of the products and services that firms offer them. This renders it expedient to consider that Game theory is a useful framework for analysing consumers' behavior in the provision of services and the impact of the co-creation of value between businesses and consumers.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Es aquella que se enfoca en los clientes como una herramienta para fortalecer dicha relación y lograr niveles adecuados de compromiso y fidelidad; generándose mayores ingresos para la empresa (Werbach & Hunter, 2012). Similarmente, existen varias empresas que ya utilizan la gamificación externa en sus estrategias empresariales como lo señalan (Gallego & De Pablos, 2013):…”
Section: • Gamificación Externaunclassified
“…Además, el uso del juego en ámbitos no tradicionales propicia condiciones de aprendizaje y rendimiento acelerado (Dignan, 2011), se compone en un eficiente vehículo para estimular cambios conductuales (Hunter R. , 2011). También, para los clientes y consumidores representa una herramienta versátil y útil dentro de la empresa, pues apoya en la identificación de tendencias humanas, atraer y retener audiencias y clientes a una marca (Gallego & De Pablos, 2013). En definitiva, la gamificación se convierte en una herramienta útil para generar cierto tipo de comportamiento o actitudes en los empleados, así como, en los clientes conocer qué características de un producto o servicio desean y fidelizarlos a una marca.…”
Section: Introductionunclassified
“…La lúdica está centrada en el aprendizaje experiencial, por lo que facilita la adquisición de habilidades que difícilmente se obtienen bajo metodologías tradicionales [18], además favorece la satisfacción, motivación [8], habilidades cognitivas, motoras, sensoriales y sociales, que aumentan la calidad de vida, la salud mental, física y social [19], incrementa la creatividad, concentración, razonamiento [20], la participación, las habilidades en resolución de problemas [21], el clima, la eficiencia, la productividad laboral y la fidelización de empleados y clientes [22], [23].…”
Section: A Lúdicaunclassified